ОНА ТИЛИ ДАРСЛАРИДА ИННОВАЦИОН ТЕХНОЛОГИЯЛАРДАН ФОЙДАЛАНИШНИНГ САМАРАДОРЛИГИ - Абдиназимов, Ш.; Тоирова, Г. (SCIENCE and SOCIETY, 2019)
The author of the article studies the effectiveness of the use of innovative technologies in the teaching of the mother tongue. In increasing the effectiveness of the course numerous games and techniques are very important. New teaching materials and educational technologies are regarded as the easiest way to get to the listener, and it can enhance the quality of the educational process.